Pharmaceutical cancer care for haematology patients on oral anticancer drugs: Findings from an economic, clinical and organisational analysis. (23rd October 2022) - Zerbit, Jeremie; Kroemer, Marie; Fuchs, Basile; Detroit, Marion; Decroocq, Justine; Vignon, Marguerite; Willems, Lise; Deau‐Fischer, Bénédicte; Franchi, Patricia; Deschamps, Paul; Contejean, Adrien; Grignano, Eric; et al.
Abstract: Objective: The clinical benefit of pharmaceutical cares in improving the quality‐of‐care outcomes is well demonstrated. Clinical pharmacy services are not systematically deployed in cancer units in the absence of economic data. The aim of this prospective, observational 1‐year study was to evaluate the clinical, economic and organisational impacts of pharmaceutical care into a multidisciplinary day hospital for patients treated with oral cancer drugs. Methods: All pharmacists' interventions (PI) were documented and their impact and the probability of adverse drug events were assessed using the clinical, economic and organisational tool. Results: Among 360 admissions, an average of 1.81 PI per admission was accepted. Among 452 PI leading to a clinical benefit on the patient, 16.9% had a major impact, and 1.9% had an impact on survival. The large majority of PIs (87%) increased the quality‐of‐care organisation. The budget impact model showed a total cost savings and cost avoidance of €539, 047 per year and a cost–benefit ratio of 7.07:1. The direct cost–benefit was €201, 741, and the cost avoidance was €337, 306. Conclusion: Multidisciplinary care and pharmaceutical care are key elements to improve cancer patients' outcomes and avoid evitable healthcare costs.